Aminoguanidine Reverses the Loss of Functional Hyperemia in a Rat Model of Diabetic Retinopathy - Mishra, Anusha; Newman, Eric A. (Frontiers in Neuroenergetics, 2012)
Flickering light dilates retinal arterioles and increases retinal blood flow, a response termed functional hyperemia. This response is diminished in diabetic patients even before the appearance of overt clinical retinopathy. The loss of functional hyperemia could deprive retinal neurons of oxygen and nutrients, possibly exacerbating the development of diabetic retinopathy. We have tested whether inhibiting inducible nitric oxide synthase (iNOS) reverses the loss of functional hyperemia in diabetic rat retinas in vivo. Changes in retinal arteriole diameter were measured following diffuse flickering light stimulation in control rats, streptozotocin-induced type 1 diabetic rats and diabetic rats treated with aminoguanidine (AG; an iNOS inhibitor), either acutely via IV injection or chronically in drinking water. Flickering light evoked large arteriole dilations (10.8 ± 1.1%) in control rats. This response was diminished by 61% in diabetic animals (4.2 ± 0.3%). Both acute and chronic treatment with AG restored flicker-induced arteriole dilations in diabetic rats (8.8 ± 0.9% and 9.5 ± 1.3%, respectively). The amplitude of the corneal electroretinogram b-wave was similar in control and diabetic animals. These findings demonstrate that inhibiting iNOS with AG is effective in preventing the loss of, and restoring, normal functional hyperemia in the diabetic rat retina. Previous work has demonstrated the efficacy of iNOS inhibitors in slowing the progression of diabetic retinopathy. This effect could be due, in part, to a restoration of functional hyperemia.